2009
DOI: 10.1002/lt.21886
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of fully covered self-expandable metallic stents in biliary complications after liver transplantation: A preliminary study

Abstract: After liver transplantation, the most common biliary complication is the anastomotic stricture, which is followed by biliary leakage. Studies have focused on the endoscopic treatment of biliary complications in transplanted patients with duct-to-duct reconstruction, showing a success rate of 70% to 80% after orthotopic liver transplantation and of 60% after living-related liver transplantation. Once the endoscopic approach fails, surgical treatment with a Roux-en-Y choledochojejunostomy is the sole alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
3
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 23 publications
7
116
3
12
Order By: Relevance
“…Aside from these two approaches (sphincterotomy alone and sphincterotomy with plastic stent placement), some authors also advocate the use of FCSEMS for patients with bile leaks (mainly post-cholecystectomy leaks) given the high resolution rates (93%-95%) in early studies. 26,27,38,39 In our clinical experience FCSEMS are useful in some LT recipients with large or refractory bile leaks, though FCSEMS were not placed during the present study. While FCSEMS may be effective for bile leaks, some stents carry a risk of new stricture formation in LT recipients, thus more information is needed in these patients.…”
Section: Discussionmentioning
confidence: 88%
“…Aside from these two approaches (sphincterotomy alone and sphincterotomy with plastic stent placement), some authors also advocate the use of FCSEMS for patients with bile leaks (mainly post-cholecystectomy leaks) given the high resolution rates (93%-95%) in early studies. 26,27,38,39 In our clinical experience FCSEMS are useful in some LT recipients with large or refractory bile leaks, though FCSEMS were not placed during the present study. While FCSEMS may be effective for bile leaks, some stents carry a risk of new stricture formation in LT recipients, thus more information is needed in these patients.…”
Section: Discussionmentioning
confidence: 88%
“…Gore & Associates, Flagstaff, AZ) in 5 patients (including 3 liver transplant recipients) at a mean of 38 days after percutaneous transhepatic stent placement and without complications, although the clinical outcomes were not available. Traina et al 12 also reported an 87.5% immediate resolution rate of the biliary strictures following 2 months of endoscopic covered metal stent placement in 16 liver transplant recipients. However, clinical success rate in LDLT recipients was 60% (3 of 5 patients).…”
Section: Discussionmentioning
confidence: 93%
“…Gwon et al 19 proposed that covered stents longer than 40 mm might reduce stent migration although they removed these stents at a mean of 6.7 weeks after stent placement. On the contrary, Traina et al 12 reported 38% of stent migration rate following endoscopic placement of 16 covered retrievable stents (60-80 mm in length) during 2 months. Therefore, we assume that a longer duration of stent placement may bring about a higher risk of stent migration and, therefore, stent modification may be necessary in order to prevent stent migration.…”
Section: Discussionmentioning
confidence: 96%
“…The types of stent used in these situations continue to evolve as stent technology changes. Two studies performed by Traina et al and Kahaleh et al reported resolution of the majority of bile leaks after the use of self-expandable metal biliary stents [16,17]. However, there were instances of stent migration and stricture formation with the use of these metal stents and cost-effectiveness is questionable.…”
Section: Leaksmentioning
confidence: 98%